2019
DOI: 10.1016/j.jtho.2019.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Response to the Combination of Osimertinib and Trametinib in a Patient With EGFR-Mutant NSCLC Harboring an Acquired BRAF Fusion

Abstract: Chiu C-H. Radiation recall pneumonitis induced by epidermal growth factor receptor-tyrosine kinase inhibitor in patients with advanced nonsmall-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Our studies and others have demonstrated that targeting MEK/ERK signaling through either MEK or ERK inhibition can achieve impressive effects in overcoming acquired resistance to osimertinib in different preclinical models 8‐12 . A clinical case study reported that an osimertinib‐resistant patient with NSCLC with a B‐Raf mutation responded to the treatment with the osimertinib and trametinib combination 13 . Moreover, MEK inhibition using trametinib combined with WZ4002, another third‐generation EGFR TKI, was shown to delay the emergence of acquired resistance to WZ4002 in WZ4002‐sensitive models 14 .…”
Section: Introductionmentioning
confidence: 70%
“…Our studies and others have demonstrated that targeting MEK/ERK signaling through either MEK or ERK inhibition can achieve impressive effects in overcoming acquired resistance to osimertinib in different preclinical models 8‐12 . A clinical case study reported that an osimertinib‐resistant patient with NSCLC with a B‐Raf mutation responded to the treatment with the osimertinib and trametinib combination 13 . Moreover, MEK inhibition using trametinib combined with WZ4002, another third‐generation EGFR TKI, was shown to delay the emergence of acquired resistance to WZ4002 in WZ4002‐sensitive models 14 .…”
Section: Introductionmentioning
confidence: 70%
“…According to the authors, this reduced dose was prescribed owing to a grade 2 pyrexia, nausea, and vomiting under higher dabrafenib and trametinib doses. Dagogo-Jack and colleagues 19 also described a successful case of combined EGFR/MAP kinase pathway blockade with osimertinib 80 mg OD and trametinib 1 mg OD; as treatment-related AEs, their patient experienced grade 2 diarrhea and fatigue, along with grade 1 rash and gastrointestinal bleeding. Nevertheless, it is worth highlighting the rapid clinical improvement, the remarkable radiologically confirmed objective response, as well as the good tolerance observed in this case even using only half standard dose of dabrafenib and trametinib approved for NSCLCs harboring BRAF V600E mutations.…”
Section: Discussionmentioning
confidence: 99%
“…BRAF mutations and fusions (i.e. AGK-BRAF, ESYT2-BRAF) have recently emerged as additional mechanisms of AR to thirdgeneration EGFR TKI 2,[18][19][20] . Studies demonstrating the efficacy of concurrent inhibition of EGFR and BRAF 3 or MEK 21 in pre-clinical models have raised clinicians' expectations about overcoming AR by combining TT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the preclinical findings, a clinical case study reported that an osimertinib-resistant patient with NSCLC carrying an EGFR 19del mutation and a B-RAF fusion (AGK-BRAF) partially responded to the combination of osimertinib and trametinib during a 5-month treatment period. 46 An NSCLC patient harboring EGFR L858R, T790M and B-RAF V600E mutations that received treatment of osimertinib and dabrafenib (a B-Raf inhibitor) plus trametinib showed significantly improved clinical symptoms after 3 weeks and could stay in the outpatient department (recovery from ECOG PS of 3 to 1). All treatment-related adverse events, including a grade II rash and decreased appetite, were tolerable.…”
Section: Introductionmentioning
confidence: 99%